Achieving clinical response in postpartum depression leads to improvement in health-related quality of life. (3rd July 2021) - Gerbasi, Margaret E.; Kosinski, Mark; Meltzer-Brody, Samantha; Acaster, Sarah; Fridman, Moshe; Huang, Ming-Yi; Bonthapally, Vijayveer; Hodgkins, Paul; Kanes, Stephen J.; Eldar-Lissai, Adi
Abstract: Objective: To evaluate the health-related quality of life (HRQoL) burden associated with postpartum depression (PPD), determine the extent to which clinical response impacts HRQoL, and estimate the impact of PPD and clinical response on healthcare resource utilization (HRU) and productivity. Methods: Patient data ( n = 127) from two multicenter, randomized, double-blind, placebo-controlled phase 3 clinical trials evaluating the safety and efficacy of brexanolone injection in adults with PPD were employed for these posthoc analyses. HRQoL and health utility was assessed with the SF-36-v2 Health Survey (SF-36v2) acute version. The 17-item Hamilton Rating Scale for Depression (HAMD-17) total score was used to identify clinical response (≥50% reduction in HAMD-17 total score). Baseline HRQoL burden was assessed by comparison to age- and gender-adjusted population normative data from the 2009 QualityMetric PRO Norming study. The impact of clinical response was evaluated by comparing day 7 and day 30 SF-36v2 scores between clinical responders and non-responders. Interpretations of the meaningfulness of clinical response were indirectly estimated via 2017 National Health and Wellness Survey data linking SF-36v2 mental component summary (MCS) scores to (HRU) and productivity. Results: Baseline HRQoL of patients with PPD was significantly below normative values. Day 7 and day 30 clinical response were associated with large and statistically significant improvements in HRQoL, greater likelihood of meeting SF-36v2 responder definitions, and reduced impairment. MCS levels corresponding to those observed in clinical responders were linked to lower HRU and productivity loss relative to non-responders. Conclusions: PPD places a substantial burden on HRQoL. Achievement of rapid clinical response (at day 7) and clinical response sustained several weeks following the end of treatment (day 30) led to significant improvement in HRQoL, suggesting the importance of identifying women with PPD and providing effective treatment options.